2021
DOI: 10.1155/2021/6683797
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Public Health Significance of Toxoplasmosis in Small Ruminants of Pastoral Community in Yabello District, Borana Zone, Southern Ethiopia

Abstract: Toxoplasmosis is a zoonotic protozoan disease. Data on seroepidemiology of toxoplasmosis in Ethiopia is scarce, almost null in the pastoral area of the Borana zone. The study was carried out to determine the seroprevalence, to identify risk factors of toxoplasmosis in sheep and goats, and to assess the awareness level of pastoralists about toxoplasmosis in the Yabello district of Borana zone, Southern Ethiopia. A cross-sectional study was conducted from November 2016 to April 2017 in six peasant associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
3
1
1
Order By: Relevance
“…The presence of cats on goat farms/flocks appeared to have a considerable influence on T. gondii prevalence and transmission [ 44 , 45 ], contrary to the current findings and to what was recorded in other investigations [ 34 , 41 , 42 ]. According to our results, the risk of contracting the infection increased not only with the presence of cats but mostly with their number on goat farms or in neighboring areas, which played an important role in maintaining parasite dissemination [ 43 , 62 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The presence of cats on goat farms/flocks appeared to have a considerable influence on T. gondii prevalence and transmission [ 44 , 45 ], contrary to the current findings and to what was recorded in other investigations [ 34 , 41 , 42 ]. According to our results, the risk of contracting the infection increased not only with the presence of cats but mostly with their number on goat farms or in neighboring areas, which played an important role in maintaining parasite dissemination [ 43 , 62 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In many regions of the world, a few studies have looked into seroprevalence and associated risk factors in traditional husbandry systems [ 43 ]. In the current study, gender was not a notable significant risk factor for exposure to T. gondii , consistent with findings from Martínez-Rodriguez et al [ 43 ] and Jilo et al [ 44 ], which showed goats of both genders were equally likely to contract a T. gondii infection. The increased incidence of T. gondii antibodies in female goats in this study might be attributable to the fact that there were more females studied than males.…”
Section: Discussionsupporting
confidence: 92%
“…According to Borana pastoralists, pets are reared as an integral part of livestock for the protection against rodents and predators. 15 In line with our findings, it has been reported that the risk of infection increases by 3 folds in farms that have dog access to the placentas and fetuses in Canada. 46 A dog is a definitive host of N. caninum and acquires the parasite by ingestion of contaminated materials, aborted fetuses, or placentas.…”
Section: Discussionsupporting
confidence: 91%
“…Cats and dogs are also an integral part of livestock for protection against predators and rodents. 15 Particularly, dogs are used as the second herdsman and kept with cattle at grazing land and watering points. Knowledge of the epidemiology of N. caninum in a pastoral setting is important for a better understanding of the impact of the disease and the implementation of the management practices that decrease the risk of exposure of cattle.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, females were found to be more susceptible to T. gondii infection in comparison to males (55.7 vs. 36.4%, respectively) in both sheep and goats. This finding is supported by several other studies [22,34,35], including a recent report conducted in Southern Ethiopia, where gender was considered a potential risk factor for the acquisition of T. gondii infection in sheep ruminants, with a higher seropositivity level reported in females than males of 67.2% versus 43.6%, respectively [39]. The higher incidence of toxoplasmosis in the ewe population is generally due to pregnancy-associated immunosuppression, lactation stress, physiological conditions, and hormonal fluctuations.…”
Section: Discussionsupporting
confidence: 85%